PENINGKATAN KEMAMPUAN BERNYANYI MELALUI SOLFEGIO DALAM PEMBELAJARAN VOKALDI MAN LUBUKALUNG - Radhiatul Fithrah; Jagar Lumban Toruan; Esy Maestro (SENDRATASIK UNP, 2012)
This studyaimed to describe the vocal learning in Extracurricular Activities through Solfegio in MAN Lubuk alung.This research is a qualitative research approach analisis. Object descriptions are vocal learning through solfegio in MAN Lubukalung. Data sourced from the observation, documentation and literature study. Once the data is collected through the data collection techniques further classifies the data based on its importance. Based on the results of research conducted at MAN Lubuk Alung in school extracurricular activitiesin the field of music, especially vocal.To improve students skills in singing, then doexercises solfegio in vocal learning. The results showed that students improved singing ability and success. Keyword: Solfegio, Vokal, Kemampuan, Bernyanyi, MAN Lubukalung